Increased interhemispheric functional connectivity after right anodal tDCS in chronic non-fluent aphasia: preliminary findings - Alemanno, Federica; Fedeli, Davide; Monti, Alessia; Houdayer, Elise; Della Rosa, Pasquale Anthony; Zangrillo, Federica; Emedoli, Daniele; Pelagallo, Elisabetta; Corbo, Massimo; Iannaccone, Sandro; Abutalebi, Jubin (Frontiers in Neuroscience, 2024)
Introduction: Anodal transcranial Direct Current Stimulation (tDCS) is a non-invasive, low-cost and environment-friendly brain neuromodulation technique that increases cortical excitability. In post-stroke aphasia, the role of the right hemisphere in language recovery remains debated. In this preliminary study, we aimed to investigate the efficacy of excitatory tDCS on the right hemisphere in chronic aphasic patients. Methods: We applied anodal tDCS to the right homologous region of Broca’s area in four chronic aphasic patients while performing a one-month naming rehabilitation treatment. Longitudinal data on language assessment and naming performance were collected. Resting-state fMRI images were acquired before and after treatment to measure changes in functional connectivity. Results: Results showed enhanced positive functional connectivity of the right Broca homologous with the left middle frontal and middle temporal gyri. Every patient showed improvements in language functions, but no major changes in naming performance. Conclusions: These preliminary findings suggest that tDCS applied over the unaffected hemisphere may result in longitudinal inter-hemispheric functional neuroplastic changes that could specifically improve language recovery and could potentially be included in therapeutic neurorehabilitative plans.